The effects of empathy by caregivers on healthcare service satisfaction - Wang, Xiaoyi; Wang, Ruining; Sheng, Feng; Chen, Leyi (Frontiers in Psychology, 2022)
Healthcare service satisfaction concentrates not only on the patients but also on the caregivers’ perspectives. This study explored how caregivers’ empathy towards the patients affects the satisfaction with the healthcare service through an electroencephalography (EEG) experiment. EEG mu rhythm was used as the neural indicator to reflect empathy. The results showed that empathy reduces caregivers’ evaluation of healthcare service satisfaction because they share sufferings with the patients. However, implementing the physician-patient communication through a process-based informed consent (IC), compared to the event-based IC, can effectively alleviate such adverse effects.